Personalizing cognitive processing therapy with a case formulation approach to intentionally target impairment in psychosocial functioning associated with PTSD - T.E. Galovski; L.B. McSweeney; R.D.V. Nixon; J.S. Wachen; B.N. Smith; S. Noorbaloochi; D. Vogt; B.L. Niles; S.M. Kehle-Forbes (Contemporary Clinical Trials Communications)
Posttraumatic stress disorder (PTSD) is a debilitating condition often accompanied by significant functional impairments affecting quality of life and well-being. While Cognitive Processing Therapy (CPT) is a leading, evidence-based psychotherapy for PTSD, demonstrating substantial efficacy in core symptom reduction, its impact on psychosocial functioning is less well-established. The Personalizing Cognitive Processing Therapy with a Case Formulation Approach (Personalizing Approaches to Therapy: PATh) study aims to enhance CPT by explicitly targeting functional impairments and idiosyncratic challenges to optimal therapy outcomes (COTOs), comparing its efficacy against standard CPT in improving psychosocial functioning, quality of life, well-being, and core PTSD and depression symptoms. This randomized controlled trial involves 200 Veterans across eight Veterans Health Administration clinical sites, assigned to either Case Formulation CPT (CF-CPT) or standard CPT. Providers will deliver up to 20 sessions per patient, with assessments at baseline, mid-treatment, post-treatment, and three months follow-up. It is hypothesized that Veterans receiving CF-CPT will show greater improvements in functioning, quality of life, well-being, and symptom reduction, alongside higher treatment completion rates compared to standard CPT. Secondary outcomes will examine specific clinical challenges and their influence on treatment outcomes. This study investigates whether a personalized, flexible CPT protocol can enhance functional recovery in PTSD treatment without compromising the efficacy of the traditional approach, potentially impacting clinical practices and patient outcomes by promoting holistic recovery for veterans with PTSD.